Organocatalytic stereoselective synthesis of passifloricin A - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2012)
The enantioselective synthesis of passifloricin A has been achieved in high diastereomeric excess. The 1,3-polyol moiety was constructed by iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes while the synthesis of lactone moiety was achieved by ring-closing metathesis (RCM).